Analysis to effectiveness e-wom at Madrasah Tsanawiyah Azzidin Medan Denai - Firmansyah, Edy; Siregar, Ilhamsyah (Junal Ilmu Manajemen, 2025)
In improving the quality of educational institutions, it is necessary to improve the abilities of teachers, education personnel, and promotional activities are required to raise the quantity and caliber of pupils to increase the number of students where promotional efforts are less effective and optimal in involving customers, so that effective promotional channels are needed by using dpromotions that directly promote by word of mouth. Madrasah Tsanawiyah Azzidin is a religious-based school equivalent to a junior high school, where this place still implements manual promotions and has not been able to utilize promotions using e-WOM, because the education personnel and marketing personnel at Madrasah Tsanawiyah Azzidin Medan cannot effectively implement e-WOM abaout the promote activities with e-WOM, where in the last 2 years the number of students at this Madrasah Tsanawiyah has tended to decrease from the original 85 students in 2022 to 73 students, so that the e-WOM service that is run is not useful and works effectively. This study's objective is to investigate and elucidate the degree to which e-WOM customer involvement and service quality influence how well e-WOM is implemented. Descriptive quantitative associative study is the methodology employed is the method of the research. The population and sample in this study amounted to 37 teachers and education personnel and marketing staff at Madrasah Tsanawiyah Azzidin Medan, where the results of the study clarified that the factors influencing e-WOM customer involvement and service quality have a partial and simultaneous to impact on how well e-WOM is implemented.